Validity and Reliability of the Objective Measure of Ego Identity Status Adaptation: The Rasch Model Approach - Nur Fadhilah Umar; M. Fiqri Syahril; Salsabila Nasution; Nurfaidah Ardis; Humairah azzahrah; Muhammad Rafli (Bulletin of Counseling and Psychotherapy, 2025)
Ego identity plays a crucial role in shaping an individual’s self-concept, career decisions, and social relationships. Accurately measuring ego identity status is essential for understanding identity formation and promoting healthy psychological development. This study examines the validity and reliability of the adapted Objective Measure of Ego Identity Status (OMEIS) using the Rasch Model, a contemporary psychometric approach that enhances measurement precision. A sample of 431 university students participated in this study, with data collected through an online questionnaire. Rasch analysis was employed to assess item fit, rating scale effectiveness, person reliability, and item difficulty levels. The results indicate that the adapted OMEIS demonstrates strong structural validity and high item reliability (0.99), although person reliability (0.63) requires improvement. The Wright Map analysis confirms the instrument’s ability to capture variations in ego identity, while item difficulty analysis highlights areas for potential refinement. Findings suggest that the Rasch Model provides a robust framework for validating psychological instruments, ensuring their applicability across diverse populations. This study contributes to the refinement of identity measurement tools and underscores the importance of advanced psychometric methodologies in psychological research